Selenium Content in the Gonads of Healthy Cats (Felis catus) and Cats with Impaired Homeostasis from the Warsaw Area (Poland) - Ewa M. Skibniewska; Michał Skibniewski (Animals, 2024)
The aim of the present study was to evaluate selenium content in the gonads of healthy cats and those with impaired homeostasis with the use of fluorescence spectroscopy. Higher concentrations of selenium were found in the gonads of the male domestic cats studied. The average content of this element in the testes of healthy males was: 0.59 mg·kg−1 while 0.47 mg·kg−1 wet weight was recorded in the ovaries of females. In the case of individuals with impaired homeostasis, higher values of selenium were found in the ovaries of obese females (0.40 mg·kg−1), while in the case of females with diagnosed malignancy of the mammary gland, the average values were lower and amounted to 0.31 mg·kg−1 wet weight of tissue. On the basis of statistical analysis, significant differences were found according to sex, age, and disturbed homeostasis of the individuals studied. An association was found between low Se in the gonads and obesity, as well as the presence of mammary gland neoplastic lesions. In addition, Se content was found to decrease with age in females, which can reduce resistance to oxidative stress.